Digital Revolution as a Strategic Innovative Challenge for Entrepreneurship - Boguslawa ZIOLKOWSKA (Communications of International Proceedings, 2021)
The development of digital technology worldwide and its repercussions for countries and entrepreneurial behaviors constitute an interesting research problem, especially that its level and pace vary significantly. In view of the above, the research objective is to determine the tendency to demonstrate entrepreneurial mindsets in three selected areas: the use of the Internet, integration of digital technology and digital public services. The aim of the studies is to find out to what extent digital revolution virtualizes entrepreneurship. In order to achieve this aim, the following questions have been posed: What are the barriers to the development of entrepreneurship that result from changes in digital technologies? What are the chances and expectations related to digital revolution? How important is digital technology and virtual space in the development of entrepreneurship? The research hypothesis: Modern information and communication technologies cause entrepreneurship to shift to cyberspace and narrow the extent to which it is pursued in the traditional form. In order to find the answers to the above questions and verify the research hypothesis, a survey was conducted. The respondents were asked to select one of the presented alternatives. The individual questions concerned the expectations and concerns connected to digital revolution, barriers to its implementation and the importance of virtual space in the development of business activity. The relationship between pro-innovation mindsets and behaviors and tendency to undertake business activity using advanced digital technologies, and between moving entrepreneurship to virtual space and resigning from carrying out business activity in the traditional form and the development of information and communication technology has been determined. The moderating impact of digital revolution on the relationships between the variables has been investigated.
Keywords: Management; Innovation; Digitalization; Entrepreneurship